PROK2/PROKR2 Signaling and Kallmann Syndrome - Dodé, Catherine; Rondard, Philippe (Frontiers in Endocrinology, 2013)
Kallmann syndrome (KS) is a developmental disease that associates hypogonadism and a deficiency of the sense of smell. The reproductive phenotype of KS results from the primary interruption of the olfactory, vomeronasal and terminal nerve fibers in the frontonasal region, which in turn disrupts the embryonic migration of neuroendocrine gonadotropin-releasing hormone (GnRH) synthesizing cells from the nose to the brain. This is a highly heterogeneous genetic disease, and mutations in any of the nine genes identified so far have been found in approximately 30% of the KS patients. PROKR2 and PROK2, which encode the G protein-coupled prokineticin receptor-2 and its ligand prokineticin-2, respectively, are two of these genes. Homozygous knockout mice for the orthologous genes exhibit a phenotype reminiscent of the KS features, but biallelic mutations in PROKR2 or PROK2 (autosomal recessive mode of disease transmission) have been found only in a minority of the patients, whereas most patients carrying mutations in these genes are heterozygotes. The mutations, mainly missense mutations, have deleterious effects on PROKR2-signaling in transfected cells, ranging from defective cell surface-targeting of the receptor to defective coupling to G-proteins or impaired receptor-ligand interaction, but the same mutations have also been found in apparently unaffected individuals, which suggests a digenic/oligogenic mode of inheritance of the disease in heterozygous patients. This non-Mendelian mode of inheritance has so far been confirmed only in a few patients. However, it may account for the unusually high proportion of KS sporadic cases compared to familial cases.